PRINCIPAL PLANNING MANAGEMENT IN INCREASING TEACHER WORK PRODUCTIVITY - Syamsu Nahar, Muhammad Syahripin, Candra Wijaya, (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: Effective educational leadership provides the basis and places goals in an important position to change norms in learning programs. This study aims to describe the planning management of school principals in increasing teacher work productivity at the Karya Bersama Halimbe Junior High School, Aek Natas District, North Labuhanbatu Regency, using a qualitative research approach. Research data collection obtained by triangulation techniques through observation, interviews and documentation study. The results of this study reveal three findings, namely: 1. Programs planned and implemented by the principal at Karya Bersama Private Junior High School in improving teacher creativity are carried out in the form of meetings / meetings or deliberations with other personnel teachers to determine plans to achieve the stated goals. Want. Then, the principal has conducted training, lesson study and participated in competitions from the district level. 2. The principal in terms of improving discipline has planned further activities to increase discipline for every month, semester or year. The existence of a meeting / meeting attended by all teachers at Karya Bersama Private Junior High School as a means of exchanging ideas between the principal and the teacher. Carry out the program that has been determined by giving awards to teachers who deserve it. 3. The planning process carried out by the principal is when holding a meeting with the principal and the teacher to compile a schedule of planning activities that have been determined until the evaluation stage carried out by the principal in developing teacher work productivity at Karya Bersama Private Junior High School. By evaluating the principal, he can see the extent of the progress experienced by teachers who have attended training and so on.